Acute drug intoxication in childhood: a 10-year retrospective observational single-centre study and case reports - Matalová, Petra; Buchta, Michal; Drietomska, Vendula; Špičáková, Alena; Wawruch, Martin; Ondra, Peter; Urbanek, Karel (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2023)
BACKGROUND: Medication poisoning in children is a severe condition that can endanger a child's life. Although drug intoxications are easily preventable, awareness of the proper handling of drugs and their safe storage out of the reach of children is not widespread among the general public. In this work, we investigated the demographic and clinical data of children admitted to the Department of Pediatrics of the University Hospital Olomouc for acute drug-induced intoxication. We also selected several case reports to illustrate the wide range of both presentations and outcomes in individual patients. METHOD: Cases of drug-induced intoxications were selected from a group of patients under the age of 19 years admitted to the hospital for poisoning between January 1, 2010, and December 31, 2019. Medical records of these patients were prospectively evaluated, and overview tables and graphs of predefined research objectives were created. RESULTS: During the given time period, 162 children with suspected drug intoxications were hospitalized at the Department of Pediatrics, University Hospital Olomouc. Of these, 108 cases were reported in girls and 54 in boys (66.7% vs. 33.3%). In 16 cases (9.9%), there was a severe intoxication requiring follow-up intensive care. There was also one case of fatal accidental intoxication. Most poisonings were seen in toddlers (65; 40.1%). Intoxication with suicidal ideation was found in 44 cases (27.2%), with a higher incidence of suicide attempts in girls (40 vs. 4). Repeated intoxication was recorded in nine cases. Analgesics were the most common drug group (61; 37.7%), with paracetamol (28; 17.3%) being the leading drug. In 154 cases (95.1%), the drugs were taken orally, most often in the form of tablets. CONCLUSION: Accidental drug intoxications most frequently occurred in the age group from one to three years old. The second highest incidence was among adolescents most of which were suicide attempts. Analgesics and psychoactive agents accounted for the majority of cases. Medications should be kept in places where children cannot reach them.
Keywords: dospělí; Hospitals; Female; Acute Disease; Infant; dítě; předškolní dítě; nemocnice; Adult; Analgesics; pokus o sebevraždu; mladý dospělý; ženské pohlaví; Adolescent; lidé; Suicide, Attempted; hospitalizace; retrospektivní studie; Male; kojenec; Hospitalization; Young Adult; Child, Preschool; analgetika; akutní nemoc; Child; mužské pohlaví; Retrospective Studies; mladiství; Humans